And What About Organizational Ethics? - Bouchard, Laurie (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
In her essay “A path forward – and outward: repositioning bioethics to face future challenges”, Vardit Ravitsky presents a vision for repositioning of bioethics in order to better face current and future challenges. While her essay has several strengths, especially the attention to inclusion, it also has an important shortcoming — there is no mention of organizational ethics.